The historical origins of knowledge society in Architecture - Kadhim, Ibrahim Jawad; Ali, Bilal Samir (Iraqi Journal of Architecture and Planning, 2018)
The research interested with studying the concept of a knowledge society in architecture, as a result of presence the concept in a speech of the Ministry of Higher Education and Scientific Research in Iraq, by calling to construction and transform to the knowledge society, to achieve educational and general societal goals. The research trying to disclosure the origins of concept in human civilizations and societies specifically who producing architectures has spatial and temporal characteristics. The research reviews the speech of the Ministry and then contemporary studies that establish the concept of knowledge society at the society, technology and economics, and then review the manifestations of the concept in architecture in order to reach a theoretical framework framed the concept within the limits of research and being The first step to solving the research problem (there is no clear perception of the fact that the concept of a knowledge society modern concept or that has historical origins in the architecture field), and it has crystallized hypothesis (the concept Associated with historical communities, representing the general social systems and systems for the production of architecture, the concept has been updated to suit the current requirements of the age). After the election two societies according to temporal and spatial frames, it has been the emergence of the theoretical framework test vocabulary formations within those communities and in their architectural production methodologies. To reach results illustrate vocabulary authentic and updated in contemporary knowledge society propositions in architecture.